Empirical and quantitative studies of Feng Shui: A systematic review (PRISMA 2009 item 1) - Ke-Tsung Han; Jin-Kai Lin (Heliyon, 2023)
Despite a long period of scholarly interest in Feng Shui, there has been no systematic review of this subject. The objective of this study was, therefore, to conduct a systematic review of empirical and quantitative Feng Shui journal articles written in Chinese or English to shed light on the nature of Feng Shui. This study identifies both existing empirical and quantitative studies of Feng Shui and directions for further research. It is the first to provide a synthesis of empirical and quantitative findings on the specific outcomes of Feng Shui, and more importantly, to explore its reliability and validity. We searched four databases, two in Chinese (Taiwan Periodical Literature and WANFANG DATA) and two in English (Web of Science and SCOPUS), and reviewed 36 articles following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA 2009). The eligibility criteria were: (1) any kind of participants or study samples; (2) any Feng Shui-related intervention; (3) comparators belonging to the same study samples or between different study samples; (4) the outcome of any empirical and quantitative measurement of Feng Shui; and (5) any study design except for qualitative studies. We used the Joanna Briggs Institute's Critical Appraisal Tools to analyze the research quality of the included articles. We found that Feng Shui was associated with housing prices in societies influenced by Chinese culture. Other findings suggested that: (1) Feng Shui was associated with the decisions of house-buyers growing up in societies influenced by Chinese culture; (2) Feng Shui forests had greater habitat diversity than other forests in China; (3) Feng Shui environments in Asia had more comfortable wind fields than non-Feng Shui settings; (4) in Asia, Feng Shui was related to sunlight; (5) Feng Shui had good reliability; and (6) Feng Shui was valid with respect to environmental features but its influence on humans has not been determined. We therefore conclude that Feng Shui is neither a superstition nor a science. Given that the research quality of the included articles was less than ideal and the number of each specific outcome and their samples were also limited, their findings should be interpreted with caution. We look forward to more good quality empirical studies of Feng Shui in the future, particularly those involving de facto field experiments recruiting non-Asian participants to provide further insights into the quasi-science of Feng Shui. (PRISMA 2009 Item 2)